2016
DOI: 10.1103/physrevb.93.045131
|View full text |Cite
|
Sign up to set email alerts
|

Bounds on corner entanglement in quantum critical states

Abstract: The entanglement entropy in many gapless quantum systems receives a contribution from corners in the entangling surface in 2+1d. It is characterized by a universal function a(θ) depending on the opening angle θ, and contains pertinent low energy information. For conformal field theories (CFTs), the leading expansion coefficient in the smooth limit θ → π yields the stress tensor 2-point function coefficient CT . Little is known about a(θ) beyond that limit. Here, we show that the next term in the smooth limit e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 129 publications
(190 reference statements)
7
57
0
Order By: Relevance
“…It was further found that even at θ = π/2 (away from the smooth limit), a 1 (π/2)/C T takes approximately the same value in a wide range of CFTs. 26,27,38 Specifically, a 1 (π/2)/C T ≈ 1.2, which nearly saturates the lower bound of (π 2 /6) ln 2 ≈ 1.14, Eq. (7).…”
Section: Properties Of the Corner Coefficientmentioning
confidence: 99%
See 3 more Smart Citations
“…It was further found that even at θ = π/2 (away from the smooth limit), a 1 (π/2)/C T takes approximately the same value in a wide range of CFTs. 26,27,38 Specifically, a 1 (π/2)/C T ≈ 1.2, which nearly saturates the lower bound of (π 2 /6) ln 2 ≈ 1.14, Eq. (7).…”
Section: Properties Of the Corner Coefficientmentioning
confidence: 99%
“…As advertised, a (M ) is determined by the first M coefficients of the smooth limit expansion of a(θ). Using recently derived bounds 38 for the coefficients σ (p) , we can explicitly show that a…”
Section: A General Boundsmentioning
confidence: 99%
See 2 more Smart Citations
“…We emphasize the fact that it is the same constant κ that appears in both divergences because the small-angle corner coefficient is also directly related to the EE of a thin strip [39,41]. It would be interesting to see if other connections exist between a(θ) and χ(θ), such as some of the bounds that apply to a(θ) [48]. In d > 3, one can also make connections between χ and higher dimensional analogues of a(θ), such as the coefficient associated with cones in 4d, however we shall not describe them here.…”
Section: A Relation To Corner Entanglementmentioning
confidence: 99%